Peran Muslimah dalam Penyelesaian Konflik - Lubis, Dahlia (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The tries to reveal the role of Muslim women (Muslimah) to mitigate conflict. The reason is that conflict resolution is often associated with males, while females have been seen hitherto as being incompetent to take a part within such important matter. One could pose a question whether women are less potent?than men?to be actors and mediators to conflict resolution or they become merely victims of every emerging conflict? Departing from this point, this article which employs bibliographical approach, attempts to expose the extent of Muslimah?s role in resolving and mitigating conflicts. It has been known that women share equal rights and responsibilities with men. However, when women deal with wide spectrum within their social activities, they have been always subordinated under the role of men. The author argues that women possess less domination than men in a number of social realms such political, educational, economical aspects. Consequently, women are viewed as biologically and socially weaker than men. Therefore, they tend to be neglected from taking role in conflict resolution.